Perbedaan Prestasi Belajar Berdasarkan Energi Sarapan, Status Gizi (IMT/U), Tingkat Pendidikan Ibu dan Tingkat Pendapatan Keluarga di SD Negeri 40 Kecamatan Pontianak Utara Provinsi Kalimantan Barat - Ginting, Septiana Maria Deba (Lembaga Penerbitan Unversitas Esa Unggul, 2015)
AbstractBackground: Breakfast provides energy intake by 20-25% of the amount of energy intake a day in order to concentrate on studying, in the long term can effect on learning achievement. Nutritional status, maternal education level, and family income level are factors also affect the learning achievement of children. Objective: Know the difference in learning achievement based energy breakfast, nutritional status (IMT/U), maternal education level, and family income level in elementary school students. Methods: 93 people were observed with cross-sectional design. Data collected was the average value of the test as a result of learning achievement, breakfast energy intake obtained through a 24-hour recall for 3 days, data mother’s education level and family income level is obtained through a questionnaire. Independent T-Test was used for statistical analysis. Result: Male gender of 47,3, female gender of 52,7%. Energy breakfast less 53,8%, adequate 46,2%. Nutritional status abnormal 16,1%, and normal 83,9%. Low maternal education 81,7%, higher 18,3%. Low family income 79,6% and higher 20,4%. Average of test scores is 55,26. There are differences in test scores of respondents with less and sufficient energy breakfast (p<0,05), there was no difference in test scores of respondent with normal nutritional status and abnormal (p≥0,05), there is a difference in test scores between children with low maternal education and higher (p<0,05), there is a difference in test scores between children with low family income and higher (p<0,05). Conclusion: School children need to familiarize the breakfast to be moreconcentrated in the study. Keywords: school children, energy breakfast, nutritional status AbstrakLatar Belakang: Sarapan memberikan asupan energi sejumlah 20-25% dari jumlah energi sehari agar mampu berkonsentrasi dalam belajar, dalam jangka panjang berpengaruh pada prestasi belajar. Status gizi, tingkat pendidikan ibu dan tingkat pendapatan orang tua merupakan faktor yang juga berpengaruh dalam prestasi belajar anak. Tujuan Penelitian: Mengetahui perbedaan hasil nilai belajar antara energy sarapan, status gizi (IMT/U), tingkat pendidikan ibu dan tingkat pendapatan keluarga pada siswa SD. Metode: Desain penelitian menggunakan desain survei observasional dan pendekatan cross-sectional, jumlah sampel 93 orang. Data yang dikumpulkan adalah nilai ujian, asupan energi sarapan, data tingkat pendidikan ibu dan pendapatan keluarga. Analisis statistik menggunakan uji T-Test Independent. Hasil Penelitian: Jenis kelamin laki-laki sebesar 47,3%, perempuan 52,7%. Energi sarapan kurang sebesar 53,8% dan cukup 46,2%. Status gizi tidak normal sebesar 16,1% dan normal 83,9%. Tingkat pendidikan ibu rendah sebesar 81,7% dan tinggi 18,3%. Tingkat pendapatan keluarga rendah sebesar 79,6% dan tinggi 20,4%. Rata-rata nilai ujian 55,26. Ada perbedaan nilai ujian berdasarkan energy sarapan kurang dan cukup (p<0,05), tidak ada perbedaan nilai ujian berdasarkan status gizi normal dan tidak normal (p≥0,05), ada perbedaan nilai ujian berdasarkan pendidikan ibu yang rendah dan tinggi (p<0,05), ada perbedaan nilai ujian berdasarkan pendapatan keluarga yang rendah dan tinggi (p<0,05). Kesimpulan: Anak sekolah perlu membiasakan sarapan agar lebih berkonsentrasi dalam belajar.Kata kunci: anak SD, energi sarapan, status gizi